Implementing posttensioned connections only in some floors of steel moment frames. (June 2021) - Heydari Tafreshi, Amir Mahdi; Gerami, Mohsen
Abstract: The studies conducted on self-centering seismic-resistant systems have largely eliminated ambiguities related to designing these types of structures. However, they have not been used well enough due to the executory differences of the structures mentioned above with those having common welded connections. The need for a specialized workforce and equipment to create posttension and install energy-dissipating elements in implementing self-center systems has made a difference in the cost of their implementation compared to conventional welding structures. The present study aims to improve the seismic behavior of steel moment frame through posttensioned energy dissipating (PTED) connections in some floors. In this regard, several states of posttensioned connections on different floors of 3 and 6-story frame are modeled by csiPerform-3d Software, and time history is used for analysis. The PF coefficient was used to evaluate the seismic performance of the frames and the PEF parameter is used to evaluate the efficiency of the pattern of setting posttensioned connections in the floors. Performing a total of 280 time history analyses on 18 frames indicates that using posttensioned connections in some floors leads to good performance while economically saving so that the seismic performance of some frames can improve more than that of the posttensioned connections-based frame performance in all floors if the best floors for setting these connections are selected. Accordingly, the use of PTED connections in all floors results in increasing 15.9% in the performance of the three-story frame, while the performance of the structure is upgraded 17.1% when PTED connections are used only in the first two floors. In addition, the results indicate that using the posttensioned connections in the lower floors of frames can improve their seismic performance and the one in the upper floors leads to a reduction in seismic performance of the frames. Accordingly, in case of using PTED connections in the two end floors of the 6-story frame, the performance of the frame reduced by 37.6%, and the frame performance reduced by 29.4% when PTED connections were used in the last three floors.